Agents of repression: the FBI's secret wars against the Black Panther Party and the American Indian Movement - Churchill, Ward (Black Classic Press, 2022)
"Daughter of the earth: song for Anna Mae Aquash" / by Ellen Klaver. -- Introduction: Beyond the myth. -- pt. I: The FBI as political police -- a capsule history. Birth and formation ; The COINTELPRO era ; COINTELPRO-Black Panther Party. -- pt. II: A context of struggle. Why Pine Ridge? ; The Pine Ridge battleground. -- pt. III: The FBI on Pine Ridge, 1972-76. The GOONs, cable splicer and garden plot ; Assassinations and bad-jacketing ; Informers, infiltrators, agents provocateurs ; The Ogala firefight ; The disinformation campaign ; Perjury and fabrication of evidence ; Other political abuses of the judicial system. -- pt. IV: We will remember. A legacy of repression ; Moving forward.